Production of 22Na isotope using a device designed to irradiate a target with the internal proton beam of the U-240 cyclotron - L. V. Mykhailov; M. V. Makovskyi; A. I. Piskarev; V. M. Shevel; Yu. V. Falchenko; L. V. Petrushynets; V. E. Fedorchuk (Ядерна фізика та енергетика)
An installation for obtaining isotopes using the intense internal beam of protons on the U-240 cyclotron has been developed. A target was designed to produce the 22Na isotope under difficult conditions of thermal and radiation loads in a limited space of the cyclotron accelerator chamber. Radiochemical isolation of the 22Na isotope was carried out.